Enhancing Human–Agent Interaction via Artificial Agents That Speculate About the Future - Casey C. Bennett; Young-Ho Bae; Jun-Hyung Yoon; Say Young Kim; Benjamin Weiss (Future Internet)
Human communication in daily life entails not only talking about what we are currently doing or will do, but also speculating about future possibilities that may (or may not) occur, i.e., “anticipatory speech”. Such conversations are central to social cooperation and social cohesion in humans. This suggests that such capabilities may also be critical for developing improved speech systems for artificial agents, e.g., human–agent interaction (HAI) and human–robot interaction (HRI). However, to do so successfully, it is imperative that we understand how anticipatory speech may affect the behavior of human users and, subsequently, the behavior of the agent/robot. Moreover, it is possible that such effects may vary across cultures and languages. To that end, we conducted an experiment where a human and autonomous 3D virtual avatar interacted in a cooperative gameplay environment. The experiment included 40 participants, comparing different languages (20 English, 20 Korean), where the artificial agent had anticipatory speech either enabled or disabled. The results showed that anticipatory speech significantly altered the speech patterns and turn-taking behavior of both the human and the agent, but those effects varied depending on the language spoken. We discuss how the use of such novel communication forms holds potential for enhancing HAI/HRI, as well as the development of mixed reality and virtual reality interactive systems for human users.